SISTEM INFORMASI GEOGRAFIS PENENTUAN PRIORITAS WILAYAH INDUSTRI DI KABUPATEN KUBU RAYA - Caroline, Priskha (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2013)
Development of industrial areas arenot regular and net appearance make invantedideas software deal with decision support systemthat can help user to choose Regional Planningof Industry in Kabupaten Kubu Raya. By usingdecision support system based geographicinformation system(GIS), thus it will be nodifficulties for a derivator decision in analyzingthe existed data. Because of gis, it will drawn theactual position of spreading data. GIS is used tivisualize a result from alternative location usedfor Regional Planning of Industry in KabupatenKubu raya. Principal component analysis andCluster Observation are the methode that use tomake a new linier combination variable fromthe real variable. To give an accurate result,variabel will reduce and produce a new variablethat called principal component. It also usecluster observation to analyzing a pattern,grouping the object into the group that has thesimilarity and classification the pattern. PCAuse to reduce variable and cluster will find thepattern and grouping the object to support theanalysis result.